2020
DOI: 10.1017/s0305741020000491
|View full text |Cite
|
Sign up to set email alerts
|

The Intermingling of State and Private Companies: Analysing Censorship of the 19th National Communist Party Congress on WeChat

Abstract: Abstract This paper examines the relationship between political events and information control on WeChat through a longitudinal analysis of keyword censorship related to China's 19th National Communist Party Congress (NCPC19). We use a novel method to track censorship on WeChat before, during and after the NCPC19 to probe the following questions. Does censorship change after an event is over? What roles do the government and private companies play in information control in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Governments ranging from Mexico to Russia have used the Internet for antisocial means, including spying or sabotaging their perceived opponents both within and outside their countries. China monitors its own citizens and thwarts antigovernment sentiments through social-media applications such as WeChat (Ruan, Knockel, Ng, & Crete-Nishihata, 2016). The United States engages in considerable surveillance of its citizens through online channels as well, the extensive nature of which we know because of whistleblower Edward Snowden’s testimony.…”
Section: Discussionmentioning
confidence: 99%
“…Governments ranging from Mexico to Russia have used the Internet for antisocial means, including spying or sabotaging their perceived opponents both within and outside their countries. China monitors its own citizens and thwarts antigovernment sentiments through social-media applications such as WeChat (Ruan, Knockel, Ng, & Crete-Nishihata, 2016). The United States engages in considerable surveillance of its citizens through online channels as well, the extensive nature of which we know because of whistleblower Edward Snowden’s testimony.…”
Section: Discussionmentioning
confidence: 99%
“…These events provide specific "sensitive" topics on which to conduct discourse analysis. In their analysis of WeChat censorship during the 19th Party Congress, Ruan et al (2020) established that "sensitive" events lead to "episodic" changes in Chinese censorship practices, which indicates that similar "episodes" might occur in the opinion guidance sphere.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research on the party-state's censorship and astroturfing strategies has concluded that, when the regime does intervene on social media, it does so largely to distract netizens from politically sensitive issues King et al (2013a) 2013b, King et al, 2014King et al, , 2017. The publication of "infotainment" during sensitive events might also be considered a form of "episodic" (Ruan et al, 2020: 3) partystate "obfuscation," as that term is applied by Brunton and Nissenbaum (2015). Thus, a comparison between official and semi-official WeChat public accounts' publication of "infotainment" -especially during the politically charged sampling period -has the potential to illuminate differences between official and semi-official vectors of "ideological guidance.…”
Section: Methodsmentioning
confidence: 99%
“…Sometimes known as WeChat. There are analytically significant differences between Weixin and WeChat which necessitate the use of one term over another (Ruan et al 2020).…”
Section: Notesmentioning
confidence: 99%